(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was conducted on twenty Gir heifers (60 days prepartum) which were randomly assigned to two experimental groups with 10 animals each. Group 1 (C) was provided nutrients as per ICAR feeding standard and group 2 (T) was provided nutrients as per ICAR feeding standard along with vitamin E (2000 IU from 60 days prepartum to 30 days postpartum and 1500 IU from 30 to 60 days postpartum) in the form of vitamin E 50% powder, (Vet Chem) supplementation and 50 g of commercial mineral mixture (Agrimin, Agrivet Farm Care Division). Body condition score (BCS) of treatment group animals were higher than control group at the time of calving and at the end of experiment. The pre-partum and post-partum changes in body weight (BW) were not apparent, but overall BW of treatment group (339.15±5.57) was higher (p value) than control group (329.79±4.58). Milk yield was similar in two groups. Calves born to mineral and vitamin E supplemented heifer had higher body weight than control group at the time of calving and after 90 days. However, the difference between the two groups was statistically not significant. It can be concluded that vitamin E and mineral supplementation during peri-partum period improved body condition score of Gir heifers and growth of their calves.